GLOBAL ENVIRONMENTAL KUZNET CURVE FACTS AND CHALLENGES FOR THAILAND ON EMISSION REDUCTION PLAN - Potipituk, Chantamon (PLANNING MALAYSIA, 2019)
The correlation between country’s gross domestic product and environment as reflected by carbon dioxide (CO2) emission, also known as environmental Kuznet Curve (KC), shows a clear indication on the country’s economic development and environmental protection status. In many aspects, economic growth and environment are not always going on a hand-in-hand mode. The most obvious example is seen in the use of natural resources to promote country’s economic development, which is stand-off one another. However, environmental Kuznet Curve has shown a fact that environmental protection can be in parallel with the economic development given that country’s economics does not largely depend on natural resources. We juxtapose the cross country data on gross domestic product (GDP) and CO2 emission from many offline and online documents. This paper explores the current facts of global environmental KC and corresponding possible consequences on Bangkok Metropolitan Emission reduction plan and implementation, towards environmentally sustainable development in Bangkok Metropolitan. By examining the global KC, three levels of development of the individual country have been identified in terms of per capita GDP and CO2 emission. It shows that most Southeast Asian countries are at initial stage of KCbased development.